Navigational Surgery of the Facial Skeleton - Schramm, Alexander; Gellrich, Nils-Claudius.; Schmelzeisen, Rainer; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Computer-assisted techniques in the surgery of the facial skeleton including the skull base are depicted for the very first time in this atlas of navigational surgery. Experienced surgeons as well as trainees will benefit from the detailed and well-illustrated information on the use of computer technology in clinical routine, accompanied by the experimental basis of intraoperative accuracy. The authors' inventions in the field of non-invasive registration have led to widespread use of computer-assisted simulation and navigational surgery in this field, so the time is right for a comprehensive publication on the topic. The interdisciplinary approach brings together maxillofacial surgeons, plastic surgeons, ENT surgeons, and neurosurgeons. New methods of non-invasive referencing and the use of virtual models in the field of oral and cranio-maxillofacial surgery are demonstrated. Clinical cases illustrate the practical use of this new technique.
Historical Evolution of Computer-assisted Surgery -- Evolution of the Clinical Use of Navigation Systems in the Head and Neck -- Intraoperative Navigation -- Registration Process -- Imaging Procedures -- Preoperative Planning and Simulation -- Preoperative Preparations -- Intraoperative Accuracy -- Patient-friendly Navigation -- Computer-assisted Therapy -- References.
Keywords: Surgery; Oral surgery; Maxillofacial surgery; Neurosurgery; Otorhinolaryngology; Otolaryngologic surgery; Plastic surgery; Surgery; Oral and Maxillofacial Surgery; Neurosurgery; Otorhinolaryngology; Head and Neck Surgery; Plastic Surgery